Reflecting on the Science of Climate Tipping Points to Inform and Assist Policy Making and Address the Risks they Pose to Society - T. F. Stocker; R. G. Jones; M. I. Hegglin; T. M. Lenton; G. C. Hegerl; S. I. Seneviratne; N. van der Wel; R. A. Wood (Surveys in Geophysics, 2025)
There is a diverging perception of climate tipping points, abrupt changes and surprises in the scientific community and the public. While such dynamics have been observed in the past, e.g., frequent reductions of the Atlantic meridional overturning circulation during the last ice age, or ice sheet collapses, tipping points might also be a possibility in an anthropogenically perturbed climate. In this context, high impact—low likelihood events, both in the physical realm as well as in ecosystems, will be potentially dangerous. Here we argue that a formalized assessment of the state of science is needed in order to establish a consensus on this issue and to reconcile diverging views. This has been the approach taken by the Intergovernmental Panel on Climate Change (IPCC). Since 1990, the IPCC has consistently generated robust consensus on several complex issues, ranging from the detection and attribution of climate change, the global carbon budget and climate sensitivity, to the projection of extreme events and their impact. Here, we suggest that a scientific assessment on tipping points, conducted collaboratively by the IPCC and the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services, would represent an ambitious yet necessary goal to be accomplished within the next decade.

Anti-drug Antibody Sample Testing and Reporting Harmonization - Darshana Jani; Robin Marsden; Michele Gunsior; Laura Schild Hay; Bethany Ward; Kyra J. Cowan; Mitra Azadeh; Breann Barker; Liching Cao; Kristin R. Closson; Kelly Coble; Sanjay L. Dholakiya; et al. (The AAPS Journal, 2022)
A clear scientific and operational need exists for harmonized bioanalytical immunogenicity study reporting to facilitate communication of immunogenicity findings and expedient review by industry and health authorities. To address these key bioanalytical reporting gaps and provide a report structure for documenting immunogenicity results, this cross-industry group was formed to establish harmonized recommendations and a develop a submission template to facilitate agency filings. Provided here are recommendations for reporting clinical anti-drug antibody (ADA) assay results using ligand-binding assay technologies. This publication describes the essential bioanalytical report (BAR) elements such as the method, critical reagents and equipment, study samples, results, and data analysis, and provides a template for a suggested structure for the ADA BAR. This publication focuses on the content and presentation of the bioanalytical ADA sample analysis report. The interpretation of immunogenicity data, including the evaluation of the impact of ADA on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Scenarios for investigating risks to biodiversity - Joachim H. Spangenberg; Alberte Bondeau; Timothy R. Carter; Stefan Fronzek; Jill Jaeger; Kirsti Jylhä; Ingolf Kühn; Ines Omann; Alex Paul; Isabelle Reginster; Mark Rounsevell; Oliver Schweiger; et al. (Global Ecology and Biogeography, 2012)
Aim This paper describes a set of integrative scenarios developed in the ALARM (Assessing LArge‐scale environmental Risks for biodiversity with tested Methods) project. The ultimate aim of ALARM was to develop and test methods and protocols for the assessment of large‐scale environmental risks to biodiversity and to evaluate mitigation options. Scenarios provide a tool for exploring such risks and the policy options to mitigate them; therefore they play a central role within the ALARM project. Methods Three integrative scenarios (liberalization, business as might be usual, sustainability) were developed and illustrated using the econometric model described in a subsequent paper. They are contextualized with projections from climate models and provide the input for model‐based assessments of biodiversity trends. Additionally, three shock scenarios were developed (Gulf Stream collapse, peak oil, pandemic) to demonstrate the limits of linear extrapolation. As these extend beyond model capabilities, they are discussed semi‐quantitatively based on modelling insights. Results Although the policy impacts on biodiversity are different for different pressures, biomes and species groups, some general trends could be identified. An extension of current EU policies will act as a brake on current trends by slowing down the loss of biodiversity in many cases and in most biomes, but it will be capable of neither halting nor of reversing the loss. Liberalization has the effect of accelerating biodiversity loss across the board, with few exceptions. A coherent sustainability scenario is clearly the most effective at preserving biodiversity, but the variant tested here still does not halt losses in all cases. Main conclusions Current EU policies for protecting biodiversity appear to be insufficient to reverse ongoing losses. Coherent sustainability strategies are effective at conserving biodiversity, but in order to assess losses and then reverse them, measures would need to be introduced that extend beyond the steps tested in the ALARM sustainability scenario.

Vascular expression, activity and function of indoleamine 2,3-dioxygenase-1 following cerebral ischaemia–reperfusion in mice - Katherine A. Jackman; Vanessa H. Brait; Yutang Wang; Ghassan J. Maghzal; Helen J. Ball; Gavin Mckenzie; T. Michael De Silva; Roland Stocker; Christopher G. Sobey (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Culture studies on the mycobiont isolated from Parmotrema reticulatum (Taylor) Choisy: metabolite production under different conditions - Alejandra T. Fazio; María D. Bertoni; Mónica T. Adler; Laura B. Ruiz; María L. Rosso; Lucia Muggia; Armin Hager; Elfie Stocker-Wörgötter; Marta S. Maier (Mycological Progress, 2009)

The influence of regional circulation patterns on wet and dry mineral dust and sea salt deposition over Greenland - M. A. Hutterli; T. Crueger; H. Fischer; K. K. Andersen; C. C. Raible; T. F. Stocker; M. L. Siggaard-Andersen; J. R. McConnell; R. C. Bales; J. F. Burkhart (Climate Dynamics, 2007)

Extreme midlatitude cyclones and their implications for precipitation and wind speed extremes in simulations of the Maunder Minimum versus present day conditions - C. C. Raible; M. Yoshimori; T. F. Stocker; C. Casty (Climate Dynamics, 2007)

Probabilistic climate change projections using neural networks - R. Knutti; T. F. Stocker; F. Joos; G.-K. Plattner (Climate Dynamics, 2003)

Constraining temperature variations over the last millennium by comparing simulated and observed atmospheric CO2 - S. Gerber; F. Joos; P. Brügger; T. Stocker; M. Mann; S. Sitch; M. Scholze (Climate Dynamics, 2003)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Link between the North and South Atlantic during the Heinrich events of the last glacial period - L. Vidal; R.R. Schneider; O. Marchal; T. Bickert; T.F. Stocker; G. Wefer (Climate Dynamics, 1999)

Thief workers and variation in nestmate recognition behavior in a ponerine ant, Ectatomma ruidum - M. D. Breed; T. P. McGlynn; E. M. Stocker; A. N. Klein (Insectes Sociaux, 1999)

Residual effects of herbicide-treated Eichhornia crassipes used as a soil amendment - Randall K. Stocker; William T. Haller (Hydrobiologia, 1999)

Abrupt climate changes: from the past to the future - a review - T. F. Stocker (International Journal of Earth Sciences, 1999)

Modelling the concentration of atmospheric CO 2 during the Younger Dryas climate event - O. Marchal; T. F. Stocker; F. Joos; A. Indermühle; T. Blunier; J. Tschumi (Climate Dynamics, 1999)

Intermittent convection, mixed boundary conditions and the stability of the thermohaline circulation - J. Hirschi; J. Sander; T. F. Stocker (Climate Dynamics, 1999)

Thiopental and midazolam do not seem to impede metabolism of glutamate in brain-injured patients - John F. Stover; Ulrike E. Pleines; Maria C. Morganti-Kossmann; Reto Stocker; Oliver S. Kempski; T. Kossmann (Psychopharmacology, 1999)